Cybernetic Serendipity : the computer and the arts. - Adrian, Marc; Allen, Roy E.; Balestrini, Nanni; Baudot, Jean A.; Bauman, Norman; Beer, Stafford; Brün, Herbert; Cage, John; Carmi, Eugenio; Cohen, John; Colin, Andrew; Connor, Raymond; et al. (New York / Washington : Frederick A. Praeger Publishers New York, 1969)
Adrian, Marc ; Agam, Yaacov ; Allen, Roy E. ; Alsleben, Kurd ; Arazi, Efraim ; Balestrini, Nanni ; Barnum, L.W. ; Baudot, Jean A. ; Bauman, Norman ; Beaman, Jeanne H. ; Beer, Stafford ; Billingsley, John ; Boeing ; Brün, Herbert ; Cage, John ; Calcomp ; Carmi, Eugenio ; Cohen, John ; Colin, Andrew ; Conner, Raymond ; Cox, Ken ; Computer Technique Group ; Csuri, Charles ; Cydac ; Dainton, Roger ; Dick, Robert ; Dowson, Mark ; Efland, Arthur ; Eschbach, Darel ; Evans, Christopher ; Forrest, A.R. ; Gainers, Stockton ; Good, Irving John ; Green, D.H. ; Harrison, L.D ; Hendricks, Leigh ; Henry, D.P. ; Hiller, Lejaren A. ; Hogle, Richard ; Honeywell ; Ihnatowicz, Edward ; Knowles, Alison ; Knowlton, Kenneth C. ; Lacey, Bruce ; Laposky, Ben F. ; Leonardo, D.J. Di ; Lifton, John ; Lull, Ramon ; Malina, Frank ; Mason, Maughan S. ; Masterman, Margaret ; Mendoza, E. ; Messinger, C.T. ; Metzger, Gustav ; Milojevic, Peter ; Morgan, Edwin ; Moscovich, Ivan ; Motors, General ; Wood, Robert McKinnon ; Nake, Frieder ; Nesbitt, Lowell ; Nes, Georg ; Noll, Michael ; O'Beirne, T.H. ; Paik, Nam June ; Palyka, Duane ; Parkin, Alan ; Pask, Gordon ; Parslow, Robert ; Penrose, Lionel ; Pierce, J.R. ; Pitteway, Michael ; Pritchett, Anthony ; Ravilious, John ; Reichardt, Jasia ; Resch, Ronald ; Riddle, Hugh ; Robbins, Donald K. ; Schillinger, Joseph ; Schmitt, Sam ; Schoffer, Nicolas ; Seawright, James ; Severtson, Johan ; Stiegler, Joseph ; Stockhausen, Karlheinz ; Strand, Kerry ; Strang, Gerald ; Sumner, Lloyd ; Szabo, John ; Tenney, James ; Tinguely, Jean ; Tsai, Wan Ying ; Weeks, John ; Wiener, Norbert ; Wiggen, Ulla ; Whitney, John H. ; Zinovieff, Peter
Engels
boek